THE DIMENSION OF EMPLOYER BRANDING: ATTRACTING TALENTED EMPLOYEES TO LEVERAGE ORGANIZATIONAL COMPETITIVENESS - Purusottama, Ambara; Ardianto, Ari (Jurnal Aplikasi Manajemen, 2019)
The challenge to meet the fulfillmentofthe workforce needs in Indonesia in the near future makes organizations immediately improve and use employer branding as an instrument of organizational competitiveness in "the war of talent". This research invites us to explore the dimensions of employer branding and also examines the dimensions towards talented local employees (students) in Indonesia. Our findings, three of five dimensions of employer branding namely working environment, company reputation, and corporate vision provide a positive and significant influence on the interest of talentedlocal employee’s career. Therefore, compensation benefitsand corporate social responsibility as part ofthe employer branding’s dimensions are not considered by talentedlocal employees in their intention to join the organization despite having a positive relationship. These findings provide insight into the importance of employer branding in maintaining the competitiveness of companies by focusing more on the intangible dimensions.